1998
DOI: 10.1046/j.1365-3156.1998.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

Trichomoniasis treatment in women: a systematic review

Abstract: SummaryOBJECTIVE To compare the effectiveness of various treatment strategies for trichomoniasis in women. DATA SOURCES Medline from 1966 to1996, Embase from 1986 to 1996, Science Citation Index from 1990 to 1996; reference lists of existing reviews; through the manufacturers of metronidazole and tinidazole in the UK, the Cochrane Controlled Trials Register until October 1997 and informal discovery. STUDY SELECTION Any randomized or quasi-randomized trial in nonpregnant women with trichomoniasis where differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…Tinidazole, another nitroimidazole, has emerged as an effective antitrichomonas medication in other countries (6). It has also been shown to be effective in clinical trials conducted in the United States (20), though it is not yet Food and Drug Administration approved.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tinidazole, another nitroimidazole, has emerged as an effective antitrichomonas medication in other countries (6). It has also been shown to be effective in clinical trials conducted in the United States (20), though it is not yet Food and Drug Administration approved.…”
mentioning
confidence: 99%
“…Differences in the pharmacokinetics of the two drugs may also play a significant role in their relative in vivo efficacies. In addition, tinidazole appears to have less severe side effects than those of metronidazole (6). Thus, broader testing of tinidazole as an The MLC was determined for each drug as described in the text.…”
mentioning
confidence: 99%
“…Given its longer halfmlife (12-14 hours versus 6-7 hours for metronidazole), 24 tinidazole would be expected to be more effective as a singlemdose therapy. It is better tolerated than metronidazole 25,26 and very cheap (wholesale price per 2 g dose ≈ US$ 0.07). Studies of singlemdose tinidazole in women with BV have shown a wide range of effectiveness (51-97%) [27][28][29][30] but used different definitions of BV and cure.…”
Section: Discussionmentioning
confidence: 99%
“…31 To treat T. vaginalis infections, WHO and others recommend as first choice, singlemdose metronidazole (2 g), 2,22,23 which has an effectiveness comparable to that of a 5-7 day course of the same drug. 25,26 Tinidazole was compared to metronidazole in early randomized trials; 32,33 a metamanalysis of these sugm m gested that singlemdose tinidazole was superior to singlemdose metronidazole. 25 We showed that singlemdose tinidazole was as effective against TV as 7 days of metronidazole.…”
Section: Discussionmentioning
confidence: 99%
“…Tinidazole 2 g orally as a single dose may also be used. Metronidazole and tinidazole have a cure rate of approximately 95% (Gülmezoglu & Garner 1998). Spontaneous cure occurs in 20-25% (Sherrard 2007).…”
Section: Treatmentmentioning
confidence: 99%